A model text recycling policy for publishers - Cary Moskovitz; Michael Pemberton; Susanne Hall (European Science Editing)
Because science advances incrementally, scientists often need to repeat material included in their prior work when composing new texts. Such “text recycling” is a common but complex writing practice, so authors and editors need clear and consistent guidance about what constitutes appropriate practice. Unfortunately, publishers’ policies on text recycling to date have been incomplete, unclear, and sometimes internally inconsistent. Building on 4 years of research on text recycling in scientific writing, the Text Recycling Research Project has developed a model text recycling policy that should be widely applicable for research publications in scientific fields. This article lays out the challenges text recycling poses for editors and authors, describes key factors that were addressed in developing the policy, and explains the policy’s main features.